Economic Methods for Lawyers - Towfigh, Emanuel; Petersen, Niels (Edward Elgar Publishing, 2015)
Responding to the growing importance of economic reasoning in legal scholarship, this innovative work provides an essential introduction to the economic tools, which can usefully be employed in legal reasoning. It is geared specifically towards those without a great deal of exposure to economic thinking and provides law students, legal scholars and practitioners with a practical toolbox to shape their writing, understanding and case preparation.